African Union Great Green Wall Initiative Experts’ and Partners’ Engagement Meeting, 13-15 May 2025, Addis Ababa - Africa Union; Accelerating Impacts of CGIAR Climate Research for Africa (2025)
This presentation was developed for the African Union (AU) Great Green Wall Initiative (GGWI) Experts’ and Partners’ Engagement Meeting which was held from the 13th - 15th May 2025 at the AU Headquarters in Addis Ababa, Ethiopia. It provides the objectives of the meeting and an overview of the AU GGWI Strategy and Ten-year Implementation Framework (2024-2034). It covers the evolution and expansion of the GGWI, its accomplishments, areas for improvement, and relevant policy linkages. It ends with an overview of the GGWI Strategic Intervention Axes and indicative priority actions for each.